1991
DOI: 10.1007/bf00023423
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an ?-amylase multigene cluster in rice

Abstract: Rice genomic clones containing eight different alpha-amylase genes have been previously classified into five groups based on DNA hybridization studies and restriction site mapping. This report describes the clustering of three Group 3 genes (RAmy3A, RAmy3B and RAmy3C) within 28 kb of genomic DNA. The genes are separated from each other by about 5 kb and transcribed in the same direction. At the protein level, RAmy3B and RAmy3C are 95% homologous while each is 78% homologous to RAmy3A. All three genes have rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

1991
1991
2004
2004

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 58 publications
0
22
0
3
Order By: Relevance
“…One of the wheat Amy3 genes, Amy3/33, is only expressed at low levels in immature seeds and no orthologous gene has been detected in barley (14). Our studies indicate that 6 of the 10 rice a-amylase genes belong to the Amy3 subfamily (8,9,21). Unlike the wheat Amy3 gene, however, members of this gene subfamily in rice are expressed in germinating seeds as well as in other tissues of the plant (8).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…One of the wheat Amy3 genes, Amy3/33, is only expressed at low levels in immature seeds and no orthologous gene has been detected in barley (14). Our studies indicate that 6 of the 10 rice a-amylase genes belong to the Amy3 subfamily (8,9,21). Unlike the wheat Amy3 gene, however, members of this gene subfamily in rice are expressed in germinating seeds as well as in other tissues of the plant (8).…”
Section: Resultsmentioning
confidence: 74%
“…Subsequently, Huang et al (20) used DNA-DNA hybridization to classify 30 rice genomic clones into five hybridization groups. These five groups were eventually consolidated into three subfamilies (Amyl, Amy2, and Amy3) on the basis of protein comparisons to other wheat and barley a-amylase genes (8,(20)(21)(22). Other investigators have used the high and low pI nomenclature to describe their cloned rice a-amylase genes (23,24).…”
mentioning
confidence: 99%
“…1B) were synthesized and used as primers. The primer extension analysis was performed according to Sutliff et al (38).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, mRNA of RAmy3B and RAmy3C has been detected in both embryo and aleurone layer of germinating rice seed. 7,11) This study demonstrated the native forms of these gene products. The degree of amino acid sequence similarity among RAmy1A, RAmy3B/3C, and RAmy3E was calculated to be 83.7 to 90.4%.…”
Section: Discussionmentioning
confidence: 66%